S53 Response to benralizumab after sub-optimal response to mepolizumab in severe eosinophilic asthma. (12th November 2019) - Kavanagh, J; Roxas, C; Green, L; Thomson, L; d'Ancona, G; Fernandes, M; Dhariwal, J; Nanzer, AM; Kent, BD; Jackson, DJ
Abstract : Introduction: Mepolizumab was the first anti-IL5 monoclonal antibody (mAb) to be licensed for severe eosinophilic asthma (SEA), and its use reduces exacerbation rate and maintenance oral corticosteroid (mOCS) requirement. A significant minority of patients fail to respond to Mepolizumab therapy, however; it is unclear if these patients may respond to other eosinophil targeting strategies, such as use of the IL5Ra mAb, Benralizumab. Methods: We retrospectively assessed patients with SEA who were switched from Mepolizumab to Benralizumab due to a sub-optimal response to the former, and had completed at least 24 weeks of treatment with the latter. We included SEA patients who had received Mepolizumab for ≥24 weeks, and had failed to achieve either a ≥50% reduction in OCS dose or a ≥50% reduction in annualised exacerbation rate (AER), or who had an ongoing requirement for ≥7.5 mg prednisolone/day. All patients had blood eosinophils of ≥0.3 in the year prior to Mepolizumab treatment. Results: Thirty-three SEA patients were included in the analysis (age 51.6±11.6, 48.5% female, BMI 32.6±7.1). Average length of Mepolizumab treatment was 42.5±11.8 weeks. At the end of Mepolizumab treatment AER was 3.94±2.13, falling to 1.71±2.22 after 24 weeks of Benralizumab (p<0.001). Twenty-nine patients were on mOCS at the end of Mepolizumab treatment, with a median daily prednisolone dose of 10 mg (IQR 5–19). By 24 weeks of Benralizumab, ten (34%) patients were able to discontinue mOCS completely, and the median dose fell to 5 mg (IQR 0–17, p=0.015). From end of Mepolizumab treatment to 24 weeks Benralizumab treatment, ACQ6 fell by 0.84 (from 3.27±1.37 to 2.43±1.35, p=0.001) and mini-AQLQ rose by 0.56 (from 3.60±1.49 to 4.16±1.45, p=0.018). Conclusion: These data suggest that a trial of Benralizumab after failure of Mepolizumab therapy may lead to significant clinical benefit in patients with SEA, with reductions in exacerbation frequency and OCS exposure, alongside improvements in patient reported outcome measures. Further investigation into the mechanisms of non-response is required, as are head to head trials to aid clinicians choosing between mAbs in SEA.